Factors determining the choice of a health centre for surgical treatment - Łepecka-Klusek, Celina; Wdowiak, Artur; Pilewska-Kozak, Anna B.; Syty, Kinga; Barlik, Justyna; Jakiel, Grzegorz (Polish Journal of Public Health, 2009)
Objective. The purpose of the study was to establish the factors determining the choice of a health centre for gynaecological surgical treatment.Material and methods. The survey covered 272 women admitted to one of four hospitals for elective gynaecological surgery during 2 months of 2008. The questionnaire used was designed for the study undertaken and tested with a pilot study carried out in the group of 25 women.Results. Regular gynaecological check-ups were confirmed by 160 (58.8%) respondents, including 44 (16.2%) - every 6 months, 75 (27.6%) – every year and 41 (15.0%) - every 2 years. The remaining 112 (41.2%) women stated they went for appointments once alarming symptoms occurred. The causes for gynaecological surgeries were divided into two groups. Group 1 included impaired function of the reproductive organ resulting in deteriorated quality of life (n=149; 54.8%), e.g. bleeding of various intensity, pain, displacement and altered stability of the reproductive organs, incontinence and procreative difficulties whereas group 2 – neoplastic diseases, e.g. malignant tumours (invading via the lymphatic system) and benign or marginal borderline tumours (n=123; 45.2%).Conclusions. The criteria of choosing a hospital providing gynaecological surgery are determined by opinions heard, e.g. high qualifications of the medical staff, modern procedures applied, equipment and/or high standard of nursing care. The main criterion of choice is significantly correlated with the place of residence, marital status and education.